2020
DOI: 10.1371/journal.pone.0236963
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Health Literacy in Southern Italy: A cross-sectional study

Abstract: Introduction Health Literacy (HL) is an important determinant of individual health. Limited HL is an increasing problem affecting the general population. This study aims to assess the level of HL in patients attending outpatient medical facilities in general medicine located in Naples and Caserta and investigate the association of HL with health behaviours and health status. Materials and methods The study involved patients attending outpatient medical facilities in general medicine. The questionnaire had four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…First of all, if the distribution of HL level in the population is consistent with results from the European Health Literacy surveys [ 3 ] and some Italian studies [ 29 , 30 ], we found higher HL level compared to other Italian studies [ 20 , 31 , 32 ]. Particularly, Lorini et al [ 20 ] using HLS–EU–Q6 found a prevalence of problematic HL level twice as high as that shown in our study.…”
Section: Discussionsupporting
confidence: 90%
“…First of all, if the distribution of HL level in the population is consistent with results from the European Health Literacy surveys [ 3 ] and some Italian studies [ 29 , 30 ], we found higher HL level compared to other Italian studies [ 20 , 31 , 32 ]. Particularly, Lorini et al [ 20 ] using HLS–EU–Q6 found a prevalence of problematic HL level twice as high as that shown in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, only a third of the study participants had adequate health literacy, which may have limited their understanding of the study materials. However, similarly low levels of health literacy were observed in another study in Italy [ 44 ], and no major issues with the final survey were detected in cognitive pilot interviews. Finally, this study was performed in a single country with only a quarter of the participants having a college education.…”
Section: Discussionsupporting
confidence: 64%
“…This gap affects life expectancy between those living in central-southern and northern regions and can reach up to three years in favor of the latter [ 34 ]. Notably, inequalities in health service delivery, in term of access to primary care across regions of the country, is well known and affects the ability of poorer performing regions to provide access to high-quality health care services [ 36 , 37 ]. Indeed, the population of the northern regions is generally more satisfied than in the past with the hospital care received; in contrast, in the central-southern regions, the level of satisfaction expressed by patients decreased from 1999 to 2017 in almost all regions [ 37 ].…”
Section: Discussionmentioning
confidence: 99%